ARBOVIRAL MENINGITIS IN CHILDREN - O. G. Kimirilova; A. A. Kimirilov; G. A. Kharchenko (Детские инфекции (Москва))
The article presents problems of optimization of diagnostics and treatment of arboviral meningitis in children. The suggestions are based on authors’ observation of 300 patients who were diagnosed with this disease and were treated in the regional infectious clinical hospital named after A.M. Nichoga,Astrakhan, in the period from 1999 till 2010.